2016
DOI: 10.2903/j.efsa.2016.4368
|View full text |Cite
|
Sign up to set email alerts
|

Safety of synthetic trans‐resveratrol as a novel food pursuant to Regulation (EC) No 258/97

Abstract: Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked for an opinion on the safety of synthetic trans-resveratrol as a novel food with a purity of ≥99% (w/w). The Panel considers that the information provided on the composition and specifications of the novel food is sufficient. The applicant intends to market the novel food as a food supplement in capsule or tablet form at daily doses up to 150 mg/day. The Panel considers that resveratrol does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…For example, the inhibitor of the cell-growth- and proliferation-regulating kinase mTOR rapamycin is an immunosuppressant and 2-deoxyglucose, which inhibits glycolysis, was cardiotoxic in rats when administered chronically 25,26 . In contrast, chronic resveratrol intake seems to be safe as stated by the European Food and Safety Authority 27 . However, not all studies observed a positive impact of resveratrol on lifespan and therefore do not support a role of resveratrol as putative CRM.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, the inhibitor of the cell-growth- and proliferation-regulating kinase mTOR rapamycin is an immunosuppressant and 2-deoxyglucose, which inhibits glycolysis, was cardiotoxic in rats when administered chronically 25,26 . In contrast, chronic resveratrol intake seems to be safe as stated by the European Food and Safety Authority 27 . However, not all studies observed a positive impact of resveratrol on lifespan and therefore do not support a role of resveratrol as putative CRM.…”
Section: Introductionmentioning
confidence: 97%
“…In 2016, the EFSA concluded that resveratrol supplements up to 150 mg/day were safe for human use 27 . Thus, we chose a dose of approximately 10 mg resveratrol (or equimolar bioacatives)/day *kg mouse.…”
Section: Introductionmentioning
confidence: 99%
“…trial was carried out prior to the feeding trial. In a first attempt to study RSV-induced changes in mice that may benefit ageing-related parameters, middle-aged mice and a dose that, considering allometric scaling [36], would be considered safe [37], were used. Since RSV application did not change mouse phenotype at a moderate dose of supplementation in 14 month old mice [35], we chose a dietary application at an approx.…”
Section: Mice Diet and Intraperitoneal Injectionsmentioning
confidence: 99%
“…It is worth mentioning the document released by the EFSA regarding the request by the European Commission on the safety of trans-resveratrol as a novel food (Efsa, 2016). In this document, the EFSA established that the 38 clinical studies provided in support of the claim do not lead to any conclusion about the efficacy of resveratrol, at doses up to 5 g/day for either acute (4 days) or chronic administration (4–12 weeks), in the treatment of metabolic diseases or cancer.…”
Section: Resveratrolmentioning
confidence: 99%